Pengaruh Pemberian Ekstrak Kulit Kacang Tanah (Arachis Hypogaea) Terhadap Kadar Trigliserida pada Tikus Putih (Rattus Norvegicus) yang diinduksi dengan Diet Tinggi Lemak - Irawan, Tannia Rizkyka; Anggoro, Joko; Priyambodo, Seto (Jurnal Kedokteran, 2017)
Background: As a way to prevent cardiovascular disease, peanut shell has been develop to be an alternative way. The present bioactive compound, luteolin, acts as antioxidant and can also influence trygliceride metabolism. The purpose of this study is to find out the effect of the peanut shell extract (Arachis hypogaea) ontriglyceride level in rats (Rattus norvegicus) induced by high fat diet. Method: Present research is an experimental research with post test control group only. The rats divided into 5 groups. They are negative control group induced by daily diet, positive control induced by simvastatin 0,9 mg/kgBB/daily, and three treatment groups induced by three different dosage of peanutshell extract (Arachis hypogaea). Three different dosage consist of 300mg/kgBB/daily (P1), 600 mg/kgBB/daily (P2), and 1200/kgBB/daily (P3) orally. Before the treatment start, we induced the rats with high fat diet 10mg/daily for 6 weeks to make hypertrygliceride state. Result: Based on the experiment, the averages of triglyceride level among KN, KP, P1, P2, and P3 are 125,8 20,4 mg/dl, 80,2 44 mg/dl, 112,4 34,6 mg/dl, 159,4 46,8 mg/dl, dan 75,4 31,9 mg/dl. Conclusion: Based on the result, it can be concluded that the oral induction of 300mg/kgBB/daily nutshell extract (Arachis hypogaea) has the same effect with simvastatin 0,19mg/kgBB/daily to lowering triglyceride level in mice with hypercholesterol state. While the oral induction of 1200mg/kgBB/daily nutshell extract (Arachis hypogaea) has the bigger effect than simvastatin 0,19mg/kgBB/daily on lowering triglyceride level in mice with hypercholesterol state.